Corpos à margem: a função do resto na psicanálise - Victor, Eugênia Assis (2021)
This work aims to discuss the function of the remainder in psychoanalysis. We run through the path from what dwells on the margins of the body to the body that dwells on the margins of the social bond. The value of the remainder impregnates and penetrates objects and people until they identify themselves with this place or manage to deal with and make other things from this remainder. We seek to approach the subject who launches himself as an object commanded by the imperative of enjoyment ( jouissance ), putting himself in risky situations, vulnerability contexts, presenting compulsive conducts of self-punishment and self-harming behaviors which can lead to death. It is a cession to a horror scene, paired with suffering. This research is based on clinical listening, and therefore we present fragments that not only illustrate the articulated concepts, but also demonstrate that it is from the clinic that they come. At first, is crafted the notion that somewhat of the experience with the body does not subscribe, there is a residue, an impossible to be said. A marginal, suppressed remainder, which is left out of the scene but has effects on it. We work with the concept of a object; we comprehend how psychoanalysis handles and deals with the remainder that falls from its knowledge, based on the comprehension that a discourse that tries to ensure unity and completeness produces its own exclusions. In a second moment, we deal with the cession of the subject to a position of worthless in his fantasy, to a reminder-place. We held a discussion on the social production of abject bodies, on the margins of the hegemonic ideal of a normal individual, happy and healthy. Finally, by working with the letter, we glimpse a way by the scripture of the remainder under analysis.